JURNAL KESEHATAN GAMBARAN TINGKAT PENGETAHUAN IBU DALAM SWAMEDIKASI DEMAM PADA BALITA DI DESA PASURENAN BATUR BANJARNEGARA - Feri Catur Yuliani S.Kep., Ns., M.Kep. (STIKES DUTAGAMA KLATEN, 2022)
Self-medication is a self-medication effort. One of the diseases that are often treated with self-medication is fever. Fever is a state of body temperature above normal temperature, which is body temperature above 37º Celsius. Fever is one of the most common health problems in toddlers. Handling fever in toddlers is very dependent on the role of parents, especially mothers. In order for proper self-medication, a mother is required to have good knowledge in dealing with fever in children. Handling fever in toddlers is very dependent on the role of parents, especially mothers. From various studies conducted in Indonesia, it is known that the level of knowledge of mothers about handling fever in toddlers varies greatly. So that the mother's level of knowledge resulted in differences in the management of fever in children. This study aims to describe the level of knowledge of fever self-medication in toddlers in Pasurenan Batur Village, Banjarnegara. The method used in this research is descriptive analytic. The number of samples taken in this study were 50 respondents using purposive sampling technique. The instrument used in this study was a questionnaire to determine the mother's level of knowledge in self-medication of fever in toddlers. The results showed that as many as 43 respondents (86%) had a good level of knowledge.